Crown: playing in the shadows - Ravlic, Tom (Wilkinson Publishing, 2022)
The glitz and glamour of casinos across the world is legendary, and Australia's Crown Casino complexes are no exception. An extensive gaming floor that is surrounded by retail outlets, food courts, accommodation and entertainment venues is the place where people come out to play.Behind the blinding lights, clinking glasses, pursuit of a winning hand or the elusive jackpot is a darker reality that lurks in the shadows about the conduct of the casino businesses like Crown across multiple jurisdictions.From sacrificing staff on the altar of profit to money laundering and breaching of gaming laws, media and government inquiries have exposed links to organised crime and the company dodged payments of gaming taxes that added further to the company's internal and public woes.Investigative journalist Tom Ravlic takes a forensic look at Crown's ills though a detailed examination of evidence presented in government reports and to commissions and inquiries. He explains how things went so wrong and explores whether there are ways of getting a fair share of the spoils from casino operations into the hands of players and the broader community